THE EFFICACY OF TRANSCRANIAL MAGNETIC STIMULATION IN TREATING TREATMENT-RESISTANT DEPRESSION: An integrative literature review - Travassos dos Santos, Nicole Maria (2025)
Major Depressive Disorder (MDD) is alarming due to its high mortality rates and its prevalence in the world population, and, once it does not respond adequately to traditional treatment, the disorder can become a Treatment Resistant Depression (TRD). Among the recommended neurostimulation methods for treatment, Transcranial Magnetic Stimulation (TMS) stands out, as a non-invasive neuromodulation technique directed to the left dorsolateral prefrontal cortex (DLPFC). The main objectives of the work were to evaluate the efficacy of TMS in the treatment of TRD, to investigate its association with other treatments and to investigate the scope of existing studies on the subject. The present Integrative Literature Review extracted data from the SciELO, PubMed and Scopus databases, with the descriptors "Transcranial Magnetic Stimulation", "Depression" and "Efficacy", including experimental, clinical, double-blind, single-blind, placebo-controlled, cohort studies, among others. It was observed among the selected articles that, in the studied populations (between 12 and 78 years), the use of TMS for the treatment of TRD is effective and safe for reducing symptoms, with different applications being tested (application frequency, intensity and time) and their interactions with antidepressants, presenting no contraindications. The results found corroborate with other more recent studies on the subject. Finally, TMS is an effective technique for the treatment of TRD in a safe way for different populations, being recommended for the reduction of depressive symptoms and improvement of the quality of life of those living with the disorder.